Revitalization of Forage Seed Production in Indonesia - Nurhayati D Purwantari (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Forage plant has multipurposes as feed, cover crop, erosion control, remediation on heavy metal contaminated soil, medicine, as well as textile and food coloring. Seed is a part of plant used for plant multiplication. National seed system covers germplasm management, breeding, seed production and its distribution. Therefore, forage seed production is an important aspect to be concerned. Forage seed production system has to produce high quality seed with optimum yield. There has not been any forage seed producer which ensures the quality of seed produced in accordance to seed certification requirement as those in food crop, horticulture or estate crop. Seed quality aspect covers genetic, physiology and physical quality. Seed stock certification is to guarantee that the distributed seeds have genetic identity, pure and high quality.